Revisão sistemática dos Enchodontidae (Euteleostei: Aulopiformes) do Brasil - Coelho, Pablo Menezes (2004)
The members of the family Enchodontidae Lydekker, 1889 show a fusiform body, strong jaws, elongate and typically caniniform teeth, and large palatine tooth. These features probably give them an active predation capacity, using those teeth to catch their preys. Enchodontid fishes are considered as inhabiting marine strict paleoenvironment, being commonly found in sedimentary deposits of the Upper Cretaceous from north Africa, south Europe, western Asia, southwestern North America, northeastern and south Brazil. In south Brazil, this family was recorded in the Atlântida Formation, Turonian of the Pelotas Basin, being recognized Rharbichthys cf. ferox and Enchodus cf. venator. Regarding Brazilian northeastern, previous records were pointed out to the Pernambuco-Paraíba and Sergipe-Alagoas basins. In the first basin, three taxa were described, as follow: E. subaequilateralis Cope, 1886, Enchodus libycus (Quaas, 1902), and E. oliveirai Maury, 1930. In the second one, E. longipectoralis (Schaeffer, 1947) and Enchodus libycus (Quaas, 1902) were described. In the present dissertation, ali material previously ascribed to the Enchodontidae was reviewed and new data were added. In addition, two new species of this family were identified in the Early Cretaceous of the SergipeAlagoas Basin. These forms were compared with severa I other enchodontid species, represented by more complete specimens from several localities. Several similarities were verified among them, suggesting that the species from the Sergipe-Alagoas Basin can be assigned to the genus Enchodus. On the other hand, these new species have some differences that allow to separate from ali known enchodontids.